Mental health dynamics between mothers and siblings of children with disabilities - Zahl, Erica; Cogo-Moreira, Hugo; Fredriksen, Trude; Kirchhofer, Solveig; Orm, Stian; Vatne, Torun; Botta, Matteo; Fjermestad, Krister (Frontiers in Psychology, 2024)
IntroductionWhen a child has a disability, their families face significant challenges that also impact parents’ and siblings’ mental health and adjustment. We examined the potential bidirectional relationships between parental mental health and sibling mental health and adjustment in families of children with a disability.MethodsWe utilized baseline and 12-month follow-up data from a randomized controlled trial of a brief intervention designed to enhance parent-sibling communication in families of children with a disability. The sample comprised 214 siblings aged 8–16 years and their parents (N = 203 mothers, N = 124 fathers). We estimated bivariate latent change score models to examine the longitudinal cross-domain associations between changes in parental mental health and changes in sibling mental health, and changes in parental mental health and sibling adjustment.ResultsThe results showed that changes in maternal mental health and sibling adjustment over the 12-month period were correlated (r = 0.22). The cross-domain associations between changes in maternal mental health and sibling mental health and adjustment were not statistically significant in any of the two models. However, baseline sibling mental health had nearly doubled impact on changes in maternal mental health (Β = 0.232, p = 0.061) compared to maternal health’s impact on sibling mental health (Β = −0.134, p = 0.289). Models with paternal mental health data unfortunately did not run due to low paternal response rate at 12-months.DiscussionThe findings suggest that whereas maternal mental health and sibling adjustment changes are correlated over time, the relationship between maternal and sibling measures does not necessarily operate bidirectionally. Future studies on family mental health dynamics should include data from fathers that may contribute to a broader understanding of these complex relationships.